2016
DOI: 10.1007/s10517-016-3406-2
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms of Carbohydrate Metabolism in Women with Different Types of Obesity

Abstract: Blood levels of glucose and immunoreactive insulin were assessed in women with android and gynoid types of obesity or normal body weight (control group) in the dynamics of oral glucose tolerance test in the morning and in the evening. In the control group, the mean concentrations of glucose and immunoreactive insulin were significantly higher in the evening at all test terms (0, 60 and 120 min), which is indicative of physiological insulin resistance in the evening. In the group of women with gynoid obesity, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
5
0
5
Order By: Relevance
“…Initial differences of carbohydrate metabolism in two groups, such as elevated levels of blood glucose and insulin in women with android obesity compared to those with gynoid obesity, are consistent with previously described characteristics of carbohydrate metabolism in women with different obesity types in response to glucose load in different phases of circadian rhythm (12). Glucose load in women with gynoid obesity was accompanied by functional hyperinsulinemia and postprandial hypoglycemia, whereas women with android obesity had absolute hyperinsulinemia, insulin resistance and hyperglycemia irrespective of the time of the day (12).The examination of women with android obesity also revealed typical disturbances of lipid metabolism manifested by initially elevated levels of LDL cholesterol and a reduced levels of HDL cholesterol, which is consistent with other authors' findings (13).…”
Section: Discussionsupporting
confidence: 88%
“…Initial differences of carbohydrate metabolism in two groups, such as elevated levels of blood glucose and insulin in women with android obesity compared to those with gynoid obesity, are consistent with previously described characteristics of carbohydrate metabolism in women with different obesity types in response to glucose load in different phases of circadian rhythm (12). Glucose load in women with gynoid obesity was accompanied by functional hyperinsulinemia and postprandial hypoglycemia, whereas women with android obesity had absolute hyperinsulinemia, insulin resistance and hyperglycemia irrespective of the time of the day (12).The examination of women with android obesity also revealed typical disturbances of lipid metabolism manifested by initially elevated levels of LDL cholesterol and a reduced levels of HDL cholesterol, which is consistent with other authors' findings (13).…”
Section: Discussionsupporting
confidence: 88%
“…The first evidence for circadian regulation of glucose metabolism emerged in the late 1960’s and 1970’s when several studies reported diurnal variations in glucose tolerance [3347]. Since then, more than a dozen human studies have reported the existence of a diurnal rhythm in oral glucose tolerance, typically peaking in the morning, with impairments in glucose tolerance in the afternoon and evening [3349]. Importantly, these time-of-day effects are independent of the fasting duration [40, 48].…”
Section: Circadian and Diurnal Rhythms In Metabolismmentioning
confidence: 99%
“…Intriguingly, diurnal rhythms in glucose tolerance, insulin levels, and peripheral insulin sensitivity are attenuated, phase delayed, or absent in obese individuals [35, 39, 49, 50] and may be altered in aged individuals [39, 54]. Moreover, they are absent or inverted ( phase delayed by several hours) in adults with type 2 diabetes [34, 35, 47, 62, 80].…”
Section: Circadian and Diurnal Rhythms In Metabolismmentioning
confidence: 99%
“…In addition, AKT phosphorylation peaks at night in mouse liver when Rev-erb α expression is lowest ( 38 , 39 ). Insulin signaling follows a circadian rhythm in humans, with a low insulin responsiveness being observed in the evening when REV-ERBα is expressed ( 40 , 41 ). These data are in line with our observation that physiologically (ZT0) or genetically induced ( Rev-erb α −/− mice) REV-ERBα depletion reduces liver OGT protein content and favors AKT phosphorylation, hence leading to increased insulin responsiveness.…”
Section: Discussionmentioning
confidence: 99%